Real earnings management of operation before and after the implementation of IFRS using cash flow measurement approach - Tiara Puspita Dewi (STIE Perbanas Surabaya, 2015)
The timeframe of this study is two years, before the implementation of IFRS in 2011 and after the implementation of IFRS in 2013. The population of this study is manufacturing companies listed in Indonesia Stock Exchange. From the existing 179 companies, 92 companies were selected according to the criteria of the sampling method and then determined as the subjects of the study. The data were secondary data obtained in the form of ready-made (provided) through publications and infor-mation issued by various organizations or public companies listed in Indonesia Stock Exchange. The focus of this study is to examine the differences in the real earnings management with the measurement of cash flow operation before and after the implementation of IFRS. Roychowdhury (2006) stated that the indication of real earnings management is the interval between -0.075 and 0.075. The results show that there is no difference between real earnings management with the measurement of cash flow operation before the implementation of IFRS and real earnings man-agement with the measurement of cash flow operation after the implementation of IFRS.